Utilizing Rainwater to Meet Clean Water Needs in Low-Cost Rusunawa Building - Arman Agung Arifin; Nurhasan Syah; Heldi; Nasfryzal Carlo; Jonni Mardizal (Postgraduate, University of Mataram, 2026)
The need for non-potable water in vertical residential buildings, especially simple rental flats (rusunawa), continues to increase along with the number of occupants and variations in domestic water use. Dependence on centralized water distribution systems makes these buildings vulnerable to supply disruptions. Therefore, an Internet of Things (IoT)-based Rainwater Harvesting (RWH) system is proposed as an alternative strategy to support sustainable non-potable water supply. This study analyzes rainfall potential, estimates domestic non-potable water demand, designs storage and distribution components, and integrates IoT-based monitoring for water level, pressure, and selected water-quality indicators. The analysis used rainfall data from the nearest relevant rainfall stations for the study area, frequency analysis with the Log Pearson Type III distribution, design discharge estimation using the Rational Method, field observation, and laboratory rainwater quality testing. The results show that the 10-year return-period rainfall is 282.624 mm/day, producing a design discharge of 0.00351 m³/s for a 1-hour rainfall duration. The daily water demand is 3.35 m³, and the proposed system uses an existing 23 m³ Ground Water Tank (GWT) and a 4.40 m³ Roof Water Tank (RWT), supported by pumps, a first-flush diverter, filtration, and a web-based IoT dashboard. Because nitrate, pH, Total Coliform, and E. coli exceed the applicable quality limits, the harvested rainwater is recommended for non-potable uses such as flushing, sanitation, and environmental cleaning after appropriate treatment.